Dilemmas and Countermeasures of Preschool Children’s Right to Education in States of Emergency - Zhang, Jing; Zhu, Li; Fei, Jiayao; Han, Mengen (Transactions on Economics, Business and Management Research, 2024)
The right to education is an inherent and inalienable fundamental human right. The importance of preschool education as the starting point of education cannot be overstated. The sudden onset of COVID-19 has disrupted traditional offline education. Furthermore, online distance learning has become a natural response to the normalization of epidemic prevention and control, and preschool education is naturally among them. Nevertheless, there are gaps in the current institutional framework, and preschool children face additional pedagogical risks in implementing online education, which makes realizing preschool children’s right to education a dilemma of low quality and inequity. Therefore, addressing the existing practical difficulties is not only a matter of urgency to guarantee the realization of the right to education for preschool children in an emergency but also a matter of necessity to improve the emergency response system.